Analisis Pendapatan Petani Jagung Pulut di Desa Lambiku Kecamatan Napabalano Kabupaten Muna - Lorensa, Tisa; Nikoyan, Anas; Gafaruddin, Abdul (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2018)
This study aims to: 1. Know the large income of farmer on corn farming in Lambiku Village, Napabalano sub-District Muna District. 2. Know the corn farming contribution to ward the farmer’s household income in Lambiku Village, Napabalano sub-District of Muna District. 3. Know the factors that affect the income of corn farmers in Lambiku Village, Napabalano sub-District Muna District. The population in this research is the entire corn farmers in Lambiku village, Napabalano sub-District Muna District as many 190 KK. The number of respondents was determined using slovin formula and the respondents were selected using simple random sampling method with error level 10%. So the total respondents were 65 farmers. The result of this research showed that the average income of corn farmers in Lambiku Village per planting season was Rp 4.204.944. The large of farmer income contribution to the total of household income is about 42,81% and the income contribution of non-farming is amount 57,19%. The factors affected income were age, farming experience, labor and capital.